Prevalence of asthmatic symptoms in Lebanese patients with type 1 diabetes and their unaffected siblings compared to age-matched controls - Taleb, Nadine (2010)
Patients with type 1 diabetes (a TH1 disease) have been reported to be at a lower risk of developing asthma (a TH2 disease). Both diseases are affected by environmental and genetic factors. Our objective is to examine this relationship in Lebanon, a Middle-Eastern country, where no previous similar studies are available. This is a cross-sectional observational study conducted at the Chronic Care Center, a referral medical center for type 1 diabetics. Patients with type 1 diabetes aged 6–39 years old, their unaffected siblings and age-matched control completed the International Primary Care Airways Group asthma screening questionnaire. The prevalence of asthma symptoms was compared among the three groups and separately within a subgroup of diabetics in relation to their carrier state of previously collected genetic data. Among 305 diabetics, 776 siblings and 187 controls, diabetics were at lower risk of having any asthma symptoms than controls; OR 0.48 (95% CI 0.32–0.72, p < 0.001) and siblings were at lower risk than diabetics and controls; OR 0.64 (95% CI 0.45–0.91, p = 0.01) and 0.28 (95% CI 0.19–0.42, p < 0.001), respectively. Among 66 diabetics, carriers of the HLA-DQB1*0201 allele were at lower risk of having any asthma symptoms than non-carriers (25.5 vs. 53.3%, p = 0.04). Only a statistically non-significant trend of higher risk was observed in carriers of HLA-DQB1*0301 and G allele at the 49 (A/G) nucleotide of CTLA-4 gene. The TH1–TH2 paradigm might partially explain these findings, since siblings were the least to report asthma symptoms. Future research is needed with diagnostic tests for asthma and extensive genetic testing.